Balancing performance and health in elite hungarian athletes: The relationship among disordered eating risk, body composition, and nutrition knowledge - Kovács, R. E.; Alpay, M.; Karsai, I.; Tornóczky, G. J.; Petróczi, A.; Boros, S. (Nutrients, 2025)
Background: disordered eating (DE) and eating disorders (ED) can negatively impact athletes` health, wellbeing, and athletic performance.